High-resolution patterning of colloidal quantum dots via non-destructive, light-driven ligand crosslinking - Jeehye Yang (Nature Portfolio, 2020)
Designing high-resolution displays based on colloidal quantum dots remains a challenge. Here, the authors demonstrate a photo-patterning method to develop CdSe-based core-shell quantum dots patterns of red, green and blue colours with diameters ranging from 7 to 20 nm and resolution of 1400 pixels per inch.